2020
DOI: 10.1002/chem.202004650
|View full text |Cite
|
Sign up to set email alerts
|

A Straightforward Synthesis of Polyketides via Ester Dienolate Matteson Homologation

Abstract: Application of ester dienolates as nucleophiles in Matteson homologations allows for the stereoselective synthesis of highly substituted α,β‐unsaturated δ‐hydroxy carboxyl acids, structural motifs widespread found in polyketide natural products. The protocol is rather flexible and permits the introduction of substituents and functionalities also at those positions which are not accessible by the commonly used aldol reaction. Therefore, this ester dienolate Matteson approach is an interesting alternative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…In consecutive Matteson homologations, the 1,2- anti -configured products are formed almost exclusively. Recently, we were also able to show that allylzinc reagents as well as ester dienolates are versatile nucleophiles in this protocol. We thus used the Matteson approach in the synthesis of a lagunamide A stereoisomer (Scheme B) …”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In consecutive Matteson homologations, the 1,2- anti -configured products are formed almost exclusively. Recently, we were also able to show that allylzinc reagents as well as ester dienolates are versatile nucleophiles in this protocol. We thus used the Matteson approach in the synthesis of a lagunamide A stereoisomer (Scheme B) …”
mentioning
confidence: 86%
“…We thus used the Matteson approach in the synthesis of a lagunamide A stereoisomer (Scheme 1B). 13 Matteson also reported that lithiated alkynes can be used, but the propargylic boronic esters obtained could not be homologated any further. 14 Also critical is the situation using vinyl organometallics, giving rise to substituted allyl boronic esters, which are very interesting synthetic intermediates.…”
mentioning
confidence: 99%
“…The idea was to introduce the two stereogenic centers on the right-hand side of lactol P via classical Matteson homologation and the unsaturated ester substituent by a recently developed ester dienolate homologation. 38 Finally, the boron atom should be removed either by protodeboronation or by oxidation/Barton−McCombie reduction. In principle, hydroxy-or other heteroatom functionalities can also be introduced at this position.…”
mentioning
confidence: 99%
“…We recently showed that ester dienolates could also be applied in the homologation step, giving access to α,β-unsaturated esters B in a highly stereoselective fashion (Scheme 1B). 19 Limitations regarding the functional groups likely result from their noncompatibility with the commonly used lithium or magnesium reagents. For example, enolates of ketones or aldehydes cannot be used in Matteson homologations, although they would provide interesting polyketide-type structures, which are generally obtained by stereoselective aldol reactions.…”
mentioning
confidence: 99%
“…Matteson proposed that enolates of sterically hindered esters , or nitriles could be used as well, but their applications are limited. We recently showed that ester dienolates could also be applied in the homologation step, giving access to α,β-unsaturated esters B in a highly stereoselective fashion (Scheme B) …”
mentioning
confidence: 99%